Novel CoTiO3/Ag3VO4 Composite: Synthesis, Characterization and Visible-light-driven Photocatalytic Activity - Kanlayawat Wangkawong (2018)
A novel CoTiO3/Ag3VO4composite is successfully synthesized by ethylene glycol-mediated route/hydrothermal method. X-ray diffraction study suggests that the composite is formed with high purity. The presence of Ag3VO4irregular agglomerates and CoTiO3rods in the composite is evidenced by field emission scanning electron microscopy and energy dispersive X-ray spectroscopy. Photocatalytic degradation experiment under visible light irradiation (λ>400 nm) indicates that the activity of Ag3VO4is significantly enhanced upon coupling with CoTiO3. Based on the obtained results, such enhanced photoactivity is mainly ascribed to the increased visible-light harvesting ability and the efficient separation of electron-hole pairs of the hybrid photocatalyst. © 2014 Elsevier B.V.